hnRNPH2 as an Inhibitor of Chicken MDA5-Mediated Type I Interferon Response: Analysis Using Chicken MDA5–Host Interactome - Lin, Xian; Yu, Shiman; Mao, Haiying; Ren, Peilei; Jin, Meilin (Frontiers in Immunology, 2020)
RIG-I and MDA5 are two key pattern recognition receptors that sense RNA virus invasion to initial type I interferon (IFN) response. Although these receptors are generally conserved among vertebrates, chicken cells lack RIG-I but have MDA5, which gives chicken MDA5 (chMDA5) a pivotal role in RNA virus sensing in chicken cells. However, different from the deep and extensive studies in mammalian MDA5, the regulation of chMDA5-mediated signaling pathway remains an unexplored area. In this study, we performed pulldown assay and mass spectrometry analysis to identify chicken proteins that could interact with the N-terminal of chMDA5 (chMDA5-N) which contained two CARDs responsible for the well-known downstream adaptor MAVS binding. A total of 337 host proteins was suggested to be potentially interacted with chMDA5-N. The factors were integrated to build a chMDA5-N-host association network and analyzed by KEGG pathway and Gene Ontology annotation. Our analysis revealed diverse cellular processes, including RNA binding and transport, protein translation, ribosomal, chaperons, and proteasome, as critical cellular factors regulating the chMDA5-mediated signaling pathway. We further cloned 64 chicken genes to investigate their effects on chMDA5-mediated chicken IFN-β production and confirmed the association of chicken DDX5, HSPA8, HSP79, IFIT5, PRDX1, and hnRNPH2 with chMDA5-N. Notably, chicken hnRNPH2 was found to impair the association of chMDA5-N and MAVS, and thus acted as a check against chMDA5 mediated signaling pathway. To our knowledge, this study is the first to analyze chicken MDA5-host interactome, which would provide a fundamental but significant data to further explore the detail mechanisms of chicken MDA5 signaling regulation.